1978
DOI: 10.1079/bjn19780162
|View full text |Cite
|
Sign up to set email alerts
|

The effects of fasting in Ramadan

Abstract: I. Fluid intake, urine output and evaporative water loss were measured and fluid balance calculated in sixteen subjects for I d before Ramadan, during weeks 1-5 of fasting and on the 10th day after the end of Ramadan.2. Plasma osmolality at 06.00 hours, the beginning of the fast, at 18.00 hours, before breaking the fast and at 19.00 hours, I h after breaking the fast, and urine osmolality during the day and night were measured before, during and after Ramadan.3. All subjects developed an initial negative fluid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(18 citation statements)
references
References 9 publications
1
14
0
Order By: Relevance
“…The decrease in athletic performance could also be partially attributed to hypo-hydration during training due to the restriction of water intake during Ramadan [32,46,47]. Hypo-hydration may also be responsible for the decrease in performance of tennis service observed during the month of Ramadan.…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in athletic performance could also be partially attributed to hypo-hydration during training due to the restriction of water intake during Ramadan [32,46,47]. Hypo-hydration may also be responsible for the decrease in performance of tennis service observed during the month of Ramadan.…”
Section: Discussionmentioning
confidence: 99%
“…If patients develop high levels of creatinine, they should end the fast immediately. Fluid deprivation may cause renal dysfunction and worsen existing renal impairment [10]; thus, patients should drink sufficient water between iftar and sleep to avoid dehydration and renal hypoperfusion. Patients should be educated about recognizing the warning symptoms of dehydration, e.g., weight loss, and about breaking fast as soon as any complication occurs.…”
Section: Discussionmentioning
confidence: 99%
“…In a globalized society, physicians may be consulted by Muslim patients with chronic diseases such as respiratory disorders who intend or insist on fasting during Ramadan (Al Wakeel et al, 2013). Nevertheless, in healthy subjects, while several studies have observed the effects of RF on body functions, such as weight, biological data (e. g., fluid and electrolyte balance, lipid levels, glucose metabolism, immunity system), sleep, and exercise (Husain, Duncan, Cheah, & Ch’ng, 1987; Margaria, Taglietti, & Agostoni, 1957; Mustafa, Mahmoud, Gumaa, & Gader, 1978; Shepard, Campbell, Martin, & Enns, 1957; Shephard, 2014; Trabelsi, Stannard, Shephard, Jamoussi, & Hakim, 2014), only a few studies have investigated its effects on spirometric data (Abdel-aziz & Ibraheem, 2008; Duncan, Husain, Raman, Cheah, & Ch’ng, 1990; Moosavi, Kabir, Moghimi, Chehrei, & Rad, 2007; Roy & Bandyopadhyay, 2016; Siddiqui, Sabir, & Subhan, 2005; Subhan, Siddiqui, Khan, & Sabir, 2006). The latter studies have some discrepancies in the findings concerning the effects of RF on pulmonary flows and/or volumes of healthy individuals.…”
Section: Introductionmentioning
confidence: 99%